Neo-Austrian modelling - Malte Faber; John Proops (University of Heidelberg, Department of Economics, 2003)
Neo-Austrian modelling is still a relatively unfamiliar technique to many ecological economists, although there is now a significant body of published work on the method and its applications. In this paper we aim to introduce the method, offering a rather brief sketch of its history, indicating how neo-Austrian models are constructed and can be applied to environmental issues, and giving a hint on some of its wider applications. We also show relationships to neoclassical growth theory.
Keywords: B53; C61; O14; Q32; 330; Neo-Austrian Capital Theory; Modelling; Ecological Economics; Environmental Economics; Input-Output-Analysis; Innovation; Umweltökonomik; Kapitaltheorie; Mehrsektoren-Modell; Input-Output-Analyse; Theorie